Soluble suppression of tumorigenicity 2 (sST2), but not galactin‐3, adds to prognostication in patients with systemic AL amyloidosis independent of NT‐proBNP and troponin T. Issue 6 (2nd April 2015) - Dispenzieri, Angela; Gertz, Morie A.; Saenger, Amy; Kumar, Shaji K.; Lacy, Martha Q.; Buadi, Francis K.; Dingli, David; Leung, Nelson; Zeldenrust, Steven; Hayman, Suzanne R.; Kapoor, Prashant; Grogan, Martha; et al.
<x xml:space="preserve">Abstract</x> The use of soluble cardiac biomarkers such as N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) and troponin has revolutionized prognostication for patients with AL amyloidosis. Soluble ST2 (sST2) and galectin‐3 have also been reported to have prognostic value in other cardiac patient populations. We identified 502 patients with AL amyloidosis, who provided a research sample and consent to review their medical records between 1/1/2006‐12/31/2010 within 90 days of their diagnosis. Samples were assayed for sST2 and galectin‐3. Within this AL amyloidosis population, overall survival (OS) was 25.5 months (95% CI 18, 35.7 months). Receiver operating curve analyses were done to detect the best cut‐points for sST2 and galectin‐3 to predict both 1‐ and 5‐year OS. The respective cut points for sST2 were 30 and 29.7 ng/mL, while the median sST2 for the entire population was 31 ng/mL (IQR 19.8, 53.6). The respective cut points for galectin‐3 were 11 and 10.4 ng/mL while the median for the entire population was 16.6 ng/mL (IQR 11.5, 24.0). Although on univariate analysis, both sST2 and galectin‐3 were prognostic, upon multivariate analysis, only sST2 was independent of troponin, NT‐proBNP, serum immunoglobulin free light chain, and blood pressure. Not only did sST2 add to previously reported prognostication systems, but a novel prognostication 5‐point system including sST2 was possible. The addition of sST2 – but not galectin‐3 – to existing prognostication systems for patients with AL amyloidosis strengthens the ability to predict for death. Am. J. Hematol. 90:524–528, 2015. © 2015 Wiley Periodicals, Inc.